The Influence of Service Quality and Educational Facilities on Student Satisfaction is Mediated by the University Image - Setyadi, Bakti; Fitriasuri, Fitriasuri; Utari, Karmila (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Universities are now competing with each other to become the institution of choice due to global competitiveness. This essay examines the relationship between student enjoyment and various qualities of university services and facilities, which are mediated by the university's reputation. A cross-sectional survey is the methodology used in studies of this kind. This type of research uses a cross-sectional survey methodology. Participants in this study were students of Bina Darma University Palembang. One hundred twenty respondents were randomly selected to represent the sample. Least squares structural equation modeling was used for data analysis (SEM-PLS). The findings of this study indicate that the existence of service quality has a positive and significant effect on student satisfaction to provide the best service and improve the quality of service to students. The accuracy of the services offered can also be seen from the feedback given by students on certain services, and the extent to which the services provided are to student expectations and the image of the University mediates between University services and student satisfaction. Hence, efforts to improve campus image positively affect student satisfaction.